EVALUATION CRITERIA LOCAL ELECTRONIC EDUCATIONAL RESOURCES - S.G. Litvinov (Kherson State University, 2013)
The article analyzes the criteria for evaluating electronic educational resources (EER), the features of the analysis, evaluation and systematization of requirements for electronic educational resources, peculiarities of design criteria determining the characteristics of the development and classification criteria for evaluating local electronic educational resources secondary schools.